Antibiotic susceptibility analysis of Escherichia coli as the cause of urinary tract infection - Melda Yunita; Hasna Vuspita Latuconsina; Eka Astuty; Alessandra Flowrence Saija (STKIP Persada Khatulistiwa Sintang, 2022)
The incidence of urinary tract infection (UTI) in Indonesia is still quite high. The UTIs are generally treated with antibiotic. However, the use of antibiotics has recently increased tremendously thus triggering bacterial resistance. This study was to analyze the susceptibility of the Escherichia coli as the cause of the UTI to 15 antibiotics at the UPTD Health Laboratory Center of Maluku Province. The study was an experimental laboratory study using the disk diffusion method. The antibiotic disc was placed on the media and the inhibition zone against E. coli was measured. The results showed that the E. coli was resistant (26.67%) to 4 types of antibiotics, namely amoxilin, ampicillin, sulfametazole dan penicillin. Meanwhile, E. coli was sensitive (46.66%) to 7 types of antibiotics, namely kanamycin, gentamicin, subactam ampicillin, chloramphenicol, amikacin, ceffazedine and azithromycin. Furthermore, E. coli was intermediate (26.67%) against 4 types of antibiotics, namely ciprofloxacin, ceptriaxone, cefoxitin and colistin. This study concluded that of the 15 antibiotics tested, gentamicin, amikacin, and kanamycin were the most effective antibiotics in inhibiting the growth of E. coli that causes UTI. Nevertheless, the appropriate choice of antibiotic needs to be adjusted only by physicians based on local, regional and national patterns of susceptibility.